Public Infrastructural Decay as An Impediment to Effective Performance - Iyiola Tomilayo Akindele; David Okanlawon; Damilare I Olusesi (Journal of Governance, 2023)
This study identified the various public infrastructural facilities—power, health, and information and communication technology (ICT)—that aid the Federal Road Safety Corps (FRSC) in performing their duty effectively. It also examined how public infrastructural decay renders Nigeria’s public service handicapped in its ability to effectively execute its goals. It adopts a survey research design technique, and a questionnaire was used to gather data. The primary data collected were analysed using descriptive statistics, while the hypothesis was tested using Pearson correlation analysis. The sample size was determined by the convenience nonprobability sampling method, and questionnaires were distributed to the respondents. The scope of the study is the FRSC Zone RS 8 Headquarters, Ilorin, Kwara State, Nigeria. The result shows that there is a weak positive relationship between adequate public infrastructural facilities and effective performance in Nigeria’s public service. It also revealed that the effective performance of Nigeria’s public service is aided by adequate public infrastructural facilities. Likewise, inadequate public infrastructural facilities slow down the effective performance of Nigeria’s public service. The study recommended that public infrastructural facilities should be taken as vital tools to enhance Nigeria’s public service performance and that public infrastructural decay should be tackled.